2011
DOI: 10.1155/2011/825636
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Neurobehavioural Status in Chronic Pain Patients

Abstract: Chronic lower back pain patients had more negative mood and less positive mood than controls. These patients also demonstrated neuromotor deficits in coordination and reaction time. Further studies are required to examine possible neurological mechanisms and research potential intervention strategies for patients suffering from chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Several studies revealed depressive symptoms and suicide risk in CPPs 19,3134. In our study, the HDRS showed a higher total score and a higher suicide-item score in the CPPs compared to the control group, thus confirming literature results.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies revealed depressive symptoms and suicide risk in CPPs 19,3134. In our study, the HDRS showed a higher total score and a higher suicide-item score in the CPPs compared to the control group, thus confirming literature results.…”
Section: Discussionsupporting
confidence: 91%
“…In Spain, prevalence is 17% (75% women) ( 3 ). Chronic pain is a complex phenomenon that is known to have a negative impact on physical ( 4 , 5 ) and psychological function ( 6 ). Individuals with chronic pain are more likely to report more fear ( 7 ), anxiety ( 8 ), depressive symptoms ( 9 ), and negative mood in general ( 10 ) than those without this condition.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesized model was constructed on the basis of a previous study 25 29 and the result of the current correlational analysis involving total social skills values, VAS, social support, and psychological factors (depression, loneliness). The hypothesis model, with standardized path coefficients, is presented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…However, loneliness in cancer patients exacerbated psychological conditions such as depression and perception of pain; 23 depression and anxiety can also increase physical pain sensitivity. 24 , 25 Thus, interactions with one’s social environment is critical for managing pain; social skills are among the personal characteristics required for adequate social interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation